Changing Perspectives: Offloading a Patient With a Diabetic Foot Ulcer as Opposed to Offloading a Diabetic Foot Ulcer. Issue 4 (August 2021) - Samuelson, Katherine L.; Kiefer, Chase T.; Wu, Stephanie C.; Crews, Ryan T.
Diabetic foot ulcers (DFUs) represent a tremendous burden to health care systems. Offloading is one of the key tenants to healing DFU and knee-high irremovable offloading devices are considered the gold standard for offloading DFU. However, the gold standard is rarely utilized in clinical practice. Patients' limited tolerance for such devices is one of a number of reasons that have been attributed to the lack of use of these devices. The practice of evidence-based medicine relies on shared decision making by pairing patients' values and preferences with the best available evidence. The present case report reviews the process of a patient-centered approach to identify the best offloading option for a patient with DFU. In consultation with the patient, a series of modalities were evaluated for offloading 2 unilateral forefoot DFUs. It is suggested that optimizing DFU offloading outcomes at the population level will require concerted efforts to employ the best offloading solution at the individual patient level. Offloading modalities are necessitated to mitigate the physical stress imparted on DFU during the weightbearing activity that patients engage in. Success is likely to be maximized by maintaining a mind-set of treating individual patients with DFUs as opposed to simply treating DFUs. Levels of Evidence: Level V: Case report